From painting to play: Bosch Adventure Game (Palíndromo, 2014)
This paper is about the Bosch Ad- venture Game produced by Boijmans Mu- seum (Rotterdam) and developed by V2_ Lab for the exhibition Hieronymus Bosch 1450-1516: Only Opportunity to See So Many Works Together. It presents a read- ing (Roland Barthes) of the interface (Lev Manovich) of the videogame, specifically, of the concept, the gameplay, the narra- tive and the Bosch’s works incorporated: The Seven Vital Sins and The Pedlar. At the end, this paper defines the videogame as a supplement of Bosch’s works and a fruition device outside of the frames of the paintings.
Keywords: museum; art; vidio game; play; Bosch